Transcutaneous electrical spinal-cord stimulation in humans - Gerasimenko, Yury (Ann Phys Rehabil Med, 2015)
Locomotor behavior is controlled by specific neural circuits called central pattern generators primarily located at the lumbosacral spinal cord. These locomotor-related neuronal circuits have a high level of automaticity; that is, they can produce a “stepping” movement pattern also seen on electromyography (EMG) in the absence of supraspinal and/or peripheral afferent inputs. These circuits can be modulated by epidural spinal-cord stimulation and/or pharmacological intervention. Such interventions have been used to neuromodulate the neuronal circuits in patients with motor-complete spinal-cord injury (SCI) to facilitate postural and locomotor adjustments and to regain voluntary motor control. Here, we describe a novel non-invasive stimulation strategy of painless transcutaneous electrical enabling motor control (pcEmc) to neuromodulate the physiological state of the spinal cord. The technique can facilitate a stepping performance in non-injured subjects with legs placed in a gravity-neutral position. The stepping movements were induced more effectively with multi-site than single-site spinal-cord stimulation. From these results, a multielectrode surface array technology was developed. Our preliminary data indicate that use of the multielectrode surface array can fine-tune the control of the locomotor behavior. As well, the pcEmc strategy combined with exoskeleton technology is effective for improving motor function in paralyzed patients with SCI. The potential impact of using pcEmc to neuromodulate the spinal circuitry has significant implications for furthering our understanding of the mechanisms controlling locomotion and for rehabilitating sensorimotor function even after severe SCI.